The Freedom of Speech Based on Jerinx Case, ITE Law Approach - Komang Vita Dianita (Catuspata, 2021)
Freedom of expression has actually been guaranteed in the law. As a citizen, having an opinion according to what is considered right is certainly a legal thing. The phenomenon of opinion in various social media is currently being loved. The thing that has often been an issue in recent weeks is the truth about the Covid-19 pandemic. Jerinx, a member of a well-known musician band in Bali, often voices opinions that are different from what actually happened. He considers that this pandemic is just a conspiracy of the global elite. The opinions expressed were conveyed through his social media channels, up to a post that forced Jerinx to go to jail for allegedly violating the rules contained in the ITE Law. The purpose of this study is to analyze the accuracy of the use of Articles in the ITE Law which is alleged to be against Jerinx for the posts he has made. By using juridical-normative research methods based on primary, secondary and tertiary legal materials such as legislation, court decisions, legal theory, and can be in the form of opinions of scholars related to existing problems. The results of this study were then analyzed qualitatively with descriptive-prescriptive presentation. There, a fact was found that all the elements of the articles of the ITE Law had been fulfilled to imprison Jerinx.